Le populisme aux Etats-Unis : la question du peuple - Jérôme Jamin (Amnis)
In this article, we explore the meaning of populism in the United States in historical perspective. We point out that if populism does not carry an ideology, it offers though a specific and original vision of the world. In the populist narrative, history and politics are scaled down to an aggressive opposition between homogeneous, in the majority and hard-working people and heterogeneous, in the minority and lazy elite. If populism is not an ideology, it annexes very easily itself on ideologies, from right to left, going sometimes towards the extremes. We illustrate the argument with US examples such as the People’s Party, Huey Long and Jesse Jackson on the left, Arnold Schwarzenegger and Donald Trump on the right, and Pat Buchanan on the extreme right. We will add a short detour with Ross Perot and the Tea Party to illustrate the specificity of fiscal populism. As a conclusion, we will show that populism is deeply rooted in the American life since the birth of the United States and the debate between the Founding fathers on the shape the Federal State should fit in the future. This will let us considering populism is not systematically a threat on democracy in the United States, and does not reduce itself to one of its possible form: far right populism.